Magnetically driven hydrogel microrobots for enhancing the therapeutic effect of anlotinib on osteosarcoma - Wang, Haoyu; Jiang, Haitian; Tao, Yining; Yang, Binghui; Shen, Jiakang; Mu, Haoran; Wang, Chongren; Yang, Xiyu; Cai, Zhengdong; Li, Mu; Sun, Wei; Yang, Liu; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Osteosarcoma is a rare malignant tumor with high mortality and disability rates. Its complex genetic background and lack of specific membrane receptors make targeted therapy for osteosarcoma difficult. Therefore, active targeting has become a promising treatment strategy for osteosarcoma.Microrobots can load drugs and travel to the desired target site under precise guidance, thereby enhancing drug efficacy while reducing damage to normal tissues. Tumors overexpressing MET exhibit acquired resistance to VEGFR-targeted drugs. SCR1481B16 is a specific MET inhibitor that has been proven to inhibit MET-driven tumor growth. This study explored the potential of magnetically driven hydrogel robots (MMHR) loaded with SCR1481B1 and Anlotinib in the treatment of Anlotinib-resistant osteosarcoma. We designed and produced microrobots that can precisely deliver drugs to tumor sites under the guidance of magnetic field, while evaluating the effect of enhancing tumor sensitivity to Anlotinib, providing new insights for the treatment of drugresistant osteosarcoma. The clinical application of this method awaits further in-depth research and validation. In conclusion, magnetically driven hydrogel microrobots loaded with SCR1481B16 provide a novel strategy for enhancing the sensitivity of Anlotinib-resistant osteosarcoma, bringing hope for future clinical applications.Osteosarcoma is the most common highly malignant bone tumor [1]. The primary treatment method is limb-salvage surgery combined with neoadjuvant chemotherapy. However, up to 90% of patients still develop drug resistance [2,3]. Patients who fail first-line treatment can only rely on second-line chemotherapy or targeted drugs to prolong their lives. However,second-line drugs also lead to